Perkembangan Riset Penerapan Analytical Hierarchy Process Pada Decision Support Systems dan Dampak Penggunaanya di Indonesia - Suryana, I Putu Agus Priska; Pramaita, Nyoman; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi Elektro, 2021)
Abstract —Decision Support Systems help decision making to solve very unstructured problems and complex. Every decision-making process always results in one final choice. In the application of decision support systems often use the Analytical Hierarchy Process (AHP) method. AHP can solve complex problems where many criteria are taken. In addition to the application of DSS, the authors also analyze the effect of implementing Decision Support Systems in an institution using simple linear regression. Simple linear regression is used to determine the effect of independent variables on the dependent variable. From several research reviews in Indonesia, many have applied the Analytical Hierarchy Process (AHP) method to assist in the decision support process. These institutions / organizations are active, in the fields of Academic, Private, Hospital, Tourism, and Government. This study found the results of the evaluation of the desktop-based AHP system development to be the most dominant with a figure of 58% where in government projects the largest was 48%. Keywords: Decision Support Systems, Analytical Hierarchy Process , AHP, Information System, Simple linear regression.